Personality Traits as Correlates of Adult Learners ’ Academic Performance in Literacy Education Centres in Ilorin, Kwara State in Nigeria - Okoji1, Onweazu Olufemi; Sulaimon, Sulaimon Damilola (Papers in Education and Development, 2021)
The purpose of this study was to find out the relationship between the five personality traits and adult learners ' academic performance in literacy education centres. The research employed correlation research design. In this study, 74 adult learners were sampled using simple random sampling technique. The researcher designed a personality traits questionnaire (with reliability index of 0.83 which was used for data collection. Data analysis was through descriptive statistics of mean to answer the research question and a linear multiple regression to test the hypothesis at 0.05 level of significance. Findings from the study revealed that majority of the adult learners were of moderate level in academic performance in Ilorin Metropolis.The combination of the independent variables significantly predicted the dependent variable (F (4, 69) = 7.273, p<0.05). Thus, it was recommended that, adult learners should always dispense good personality to their studies and approach their learning duties with zeal and enthusiasm. Keywords: adult learning, agreeableness, conscientiousness, extraversion, neuroticism